Cell junctions in fish seminiferous epithelium - Batlouni, S. R. [UNESP]; Nóbrega, R. H.; França, L. R. (Springer Nature, 2009)
Similar to mammals, in fish the cellular interactions between Sertoli cells (SC) and germ cells (GC) in the seminiferous epithelium have important structural and functional roles. In this review, we give a brief summary of these interactions, in particular those on the cell junctions. Despite the scarcity of detailed empirical data, it appears that both basic types of adhesive junctions (actin- and intermediate filaments-related) are present between SC. However, the actin-related multifunctional junction known as the ectoplasmic specialization is seemingly present only in some cartilaginous fish. Conversely, SC in other fish species are joined by actin-related junctions similar to typical zonulae or puncta adherens found in other epithelia. Adhesive junctions are also found between SC and GC and between GC and GC, and due to their particular characteristics these junctions are known as desmosome-like junctions. In terms of intercellular communication, connexins and gap junctions have been shown to occur between SC in fish, and they may be involved in the coordination of the synchronous development of GC within the cysts. It is also possible that gap junctions may form an interconnected network between SC and GC within a cyst. Concerning the SC barrier, tight junctions between fish SC apparently form a functional barrier only in cysts containing haploid GC, and different from mammals, meiotic GC in fish are not shielded from the vascular system. In summary, although still not well investigated, cell-cell interactions in the seminiferous epithelium of fish seem to be crucial for GC development, and their disturbance, for example by changing environmental conditions, will probably affect GC survival and fertility. © Springer Science+Business Media B.V. 2008.
Keywords: Adhesive junctions; Blood testis barrier; Cell junctions; Gap junctions; Seminiferous epithelium; Sertoli cell barrier; animal; cell junction; cytology; fish; histology; male; physiology; review; seminiferous tubule epithelium; Animals; Fishes; Intercellular Junctions; Male; Seminiferous Epithelium; Chondrichthyes; Mammalia